QUALITY OF LIFE FROM AMAZONAS STATE UNIVERSITY – UEA /AM STUDENTS, BRAZIL (Fiep Bulletin - online, 2016)
The objective of this study was to verify and evaluate the Quality of Life (QoL) level of university degree Physical Education, Mathematics and Pedagogy students , from  the University of the State of Amazonas – UEA, Borba/AM campus, through the instrument questionnaire SF-36, which evaluates eight distinct domains: Motor Capacity, Limitation on Physical Aspects, Pain, General Health State, Vitality, Social Aspects, Limitation on Emotional Aspects, and Mental Health. The study, classified as field, exploratory and descriptive nature, consisted of a sample of 98 subjects (49 men and 49 women), intentionally selected, aged between 18 and 43 years (average age 28.21). The results showed a satisfactory average QoL level in most of the areas - 6 of them, considering as a satisfactory level a number equal to or above 60. Only two areas showed levels below 60: General Health State (51.45), and Limitation by Emotional Aspects (57.10). Considering the results found, it is suggested that more researches are developed with the same sample, in order to identify why two of the domains had regular rates for the QoL.
Keywords: Quality of Life; University Students; SF-36